Factors That Affect The Consumptive Behavior of Paylater Users - Jamot Parasian Tambunan, Parada; Mulyati, Heti; Anggraeni, Elisa (Quantitative Economics and Management Studies, 2025)
The rapid advancement of digital transformation has led to innovations in the financial sector, one of which is the paylater service. This service has significantly influenced financial behavior, particularly among millennials in Indonesia. Paylater allows consumers to make purchases immediately and defer payments with flexible terms, making it increasingly popular due to its accessibility. The growing adoption of this service reflects a consumerist trend that may contribute to increased debt, especially in urban areas. This study aims to examine the influence of financial literacy, digital literacy, self-control, lifestyle, and financial behavior on consumer behavior in using paylater services among millennials in Bogor City. A quantitative approach was employed, involving a sample of 280 respondents from diverse age groups, occupations, and educational backgrounds. Data were collected through questionnaires and analyzed using the SEM-PLS technique with SmartPLS. The findings indicate that financial literacy, lifestyle, self-control, and financial behavior have a significant positive impact on consumer behavior, whereas digital literacy does not show a significant influence. This study provides important implications for paylater service providers, the government, and society to enhance financial literacy and self-control, promote responsible lifestyle and financial behaviors, and encourage the wise use of paylater services.